Nasihahu Ila Iblis: Mustafa Momari's Style of Speech, Clever and Poignant Satire on YouTube - Putra, Andri Sang; Basid, Abdul (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study examines the use of satirical language in the YouTube clip “Mustafa Momari Nasihuhu Ila Iblis,” a digital performance that combines satirical language with sharp socio-political messages. Interest in this topic is driven by the growing popularity of YouTube as an alternative platform for political expression in the Arab world. Creators use satire to implicitly criticize those in power through multimodal communication. The main objectives of this study are to identify the types of satirical language used, examine the context of its development, and describe its role in the development of socio-political commentary. Data were collected through a qualitative descriptive approach and stylistic analysis, based on Gorys Keraf's theory of satirical language, to identify satirical utterances. The results of the analysis show that there are six types of satire: irony (6 data), cynicism (7), sarcasm (9), satire (5), innuendo (5), and antithesis (3). Sarcasm was identified as the most dominant type. These findings confirm that Momari's satirical style is effective in criticizing Saudi Arabian leadership and various socio-political issues in the Arab-Islamic world. This study contributes to Arabic language studies by demonstrating the relevance of stylistics in explaining contemporary digital language. Future research should focus on developing multimedia analysis or cross-platform comparisons to gain deeper insights into the function of satirical language styles and the role of satire in digital political communication.